Biological functional annotation of retinoic acid alpha and beta in mouse liver based on genome-wide binding - He, Yuqi (American Physiological Society, 2014)
Retinoic acid (RA) has diverse biological effects. The liver stores vitamin A, generates RA, and expresses receptors for RA. The current study examines the hepatic binding profile of two RA receptor isoforms, RARA (RARα) and RARB (RARβ), in response to RA treatment in mouse livers. Our data uncovered 35,521, and 14,968 genomic bindings for RARA and RARB, respectively. Each expressed unique and common bindings, implying their redundant and specific roles. RARB has higher RA responsiveness than RARB. RA treatment generated 18,821 novel RARB bindings but only 14,798 of RARA bindings, compared with the control group. RAR frequently bound the consensus hormone response element [HRE; (A/G)G(G/T)TCA], which often contained the motifs assigned to SP1, GABPA, and FOXA2, suggesting potential interactions between those transcriptional factors. Functional annotation coupled with principle component analysis revealed that the function of RAR target genes were motif dependent. Taken together, the cistrome of RARA and RARB revealed their extensive biological roles in the mouse liver. RAR target genes are enriched in various biological processes. The hepatic RAR genome-wide binding data can help us understand the global molecular mechanisms underlying RAR and RA-mediated gene and pathway regulation.